Implementation of a passive automatic focusing algorithm for digital still camera - Lee, Je-Ho; Kim, Kun-Sop; Kwon, Yong-Mu; Kim, Hyoung-Gon (Digest of Technical Papers - IEEE International Conference on Consumer Electronics, 1995)
In this paper, we propose a passive AF algorithm based on two-stage focusing process where two different focus measures are used. With the paraxial geometric optics models of image formation, we investigate some well-known focus measures and derive a robust focusing technique with them.